A Survey of the Active Intellect in Transcendent Theosophy. (17th September 2018) - Salem, Maryam; Kheradmand, Maryam
Abstract : Mullā Ṣadrā (1572–1640) can, as we will argue in this article, be considered the greatest philosopher in Islamic world, because he has tried to eliminate the shortcomings of all previous schools. He claimed that man unites with the Active Intellect in the process of his intellectual perception, which is the highest perceptive status of the soul. This union, in its intense form, dissolves the human soul in the Active Intellect. In this theory, Mullā Ṣadrā assimilates some specific principles which belong only to what Seyyed Hossein Nasr has defined as Transcendent Theosophy: the primacy of existence, graded unity of being, substantial motion, the evolutional motion of the soul in all perceptive steps, the unity of the intellect, the intelligent, and the intellegible and identity of knowledge and being. Since the Active Intellect is the archetype of humanity from Mullā Ṣadrā's view, i.e. among the horizontal intellects or the same Platonic Ideas, and there is no plurality in the world of intellect, the main problem raised is how an Active Intellect is distinguished from other intellects, and the human soul is united with and eventually destroyed. Hence, Mullā Ṣadrā, in his theory of expanded emanation, envisages that the plurality of the universe is due to the quiddity, which is an ideational (ʾiʿtibāri) thing. Thus, according to him, we can say that the plurality of the world of the intellect is subjective and comes to the fore to justify the relation of God to the world of pluralities; so the theory of intellects is based on the substantive and natural view into the universe, which is the general view of the philosophers; however, the theory of expanded emanation is a particular view of Mullā Ṣadrā, which is in full harmony with important philosophical foundations of him. The present study tries to explain these issues through Mullā Ṣadrā's texts.